Hit and jump Circuit Game to Stimulate the Concentration to 5 to 6 -Year -Old Children - Susanti, Ni Putu Desy; Putu Rahayu Ujianti; Rendy Setyowahyudi (Jurnal Pendidikan Anak Usia Dini Undiksha, 2025)
Kindergarten teachers experience obstacles and difficulties when developing appropriate media to stimulate the concentration of children aged 5-6 years. Children find it very difficult to concentrate and their minds are easily distracted. Therefore, activities are needed that can train children's concentration skills. The purpose of this study was to prove the effectiveness of the hit and jump circuit game for children aged 5-6 years. This type of research is development research. The research model used is the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The subjects of this study were 20 kindergarten children. This study used a questionnaire collection method and used an observation questionnaire (non-test). The instruments used were observation sheets and questionnaire sheets. The data analysis technique used was quantitative descriptive analysis and inferential statistics. The results of the effectiveness test obtained a tcount of 33.65. Then ttable with db = n-1 = 20-1 = 19. The ttable value for db 19 with a significance level of 5% (α = 0.05) is 1.685. Thus, the results of the analysis can be compared that tcount is greater than ttable so that H0 is rejected and H1 is accepted. So it can be concluded that the hit and jump circuit game is effectively applied to stimulate the concentration of children aged 5-6 years. The implications of this study are expected to be a reference for teachers in kindergartens in choosing activities that can stimulate children's concentration.